(untitled) (Vietnam Journal of Community Medicine, 2024)
Objective: Describe the epidemiological characteristics, computed tomography, and surgical results of traumatic epidural hematoma in children. Subjects and methods: A cross-sectional descriptive study on 33 pediatric patients, diagnosed with supratentorial epidural hematoma, operated on at Thai Nguyen Central Hospital from October 2020 to February 2024. Result: In 33 cases of supratentorial epidural hematoma, the average age was 11.3 years old, 57.6% were male, 42.4% were female. The cause of injury was due to traffic accidents 72.7%, and falls 24.2%. CT scan shows that epidural hematoma in multiple locations (≥2) accounted for the highest rate of 63.6%, 45.5% of patients did not record midline shift on CT scan, 33% had midline shift of 6-10mm, hematoma volume was between 30 -50gr (66.7%), source of bleeding: Skull fracture causing epidural hematoma (63.6%), average hospital stay was 11.96 days, longest was 18 days. All patients were conscious upon discharge. Surgical results after 6 months evaluated according to GOS scale: Grade I: 87.9%; Grade II: 9.1%; Grade III: 3.0%. Conclusion: Traffic accidents account for a high proportion of the causes. Surgery to treat epidural hematoma in children at Thai Nguyen Central Hospital has good results. The method of opening the skull to remove the hematoma, stop the bleeding, and reposition the bone during surgery is the commonly chosen method, and is still highly effective in treatment.